HUBUNGAN SOSIALEKONOMI PERSATUAN OJEK NAGARI TAMBANGAN DI KECAMATAN X KOTO KABUPATEN TANAH DATAR - Erna Junita; Basri " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This adult transportasion that practical community was very helpful in reaching many facilities.Are using the community instrument transporting city transport, vilage transportation, taxi, taxi operators and other. Taxi operators is one of means of transportation for being an ideal more practical,saves time,cost-effective and used by all the community. At first the seller motorcycle taxi work individualy, as time goes and the increasing number of a person needs motorcycle taxi ,including the tambangan then formed a community where named unity taxi Nagari Tambangan ( the porta ). The establishment of the community this reason for being an porta want to help the people in transportation and meet the needs of the economy for the seller motorcycle taxi. Highlights the difficulty in this research is (1) how the from of social relations and economic taking place in the porta Kecamatan X Koto Kabupaten Tanah Datar ? (2) how did the from of conflicts that have occurred on the members of the porta in Kecematan X Koto Kabupaten Tanah Datar ? The purpose of this research is to find social relations and unity economic on taxi Nagari Tambangan di Kecematan X Koto Kabupaten Tanah Datar. To know the from of conflicts that have occured in taxi Nagari Tambangan. Respondents in this research was all members of the seller motorcycle taxi that join within the community the porta. Consisting of 35 respondents research seller taxi services porta.Which is housed in the Tambangan.This method is carried out  in a quantitative descriptif. The process of data collection in an interview that observation and documentation. The social economy is minang people running at the porta. The average this group is always active in the community even though they have the group it self.  The  also does porta various ways so that this community has stayed as with conducting activities arisan, saving and loan, mutual aid  and meeting every wo monthsto discuss how they comfort costumers. This group also tenacious in overcoming a problem that occurs as external conflict which happened screamble for customers misunderstand, and less of trust between a fellow member. This group resolve the conflict in a deliberative manner,perform peace and give sanction  conforming to a norm that applies as by means of removing them from the group.keyword: social relationships, taxi economic unity